Sex Difference in Access to Sports: A 1-Year Retrospective Study. Issue 1 (January 2021) - Nasi, Milena; D'alisera, Roberta; Cossarizza, Andrea; Guerra, Emanuele; Savino, Gustavo; Mattioli, Anna Vittoria
Purpose. Regular physical activity is a cornerstone in the prevention and treatment of cardiovascular disease thanks to its anti-inflammatory effects. Thus, favoring the access to sports is of importance for promoting well-being. The aim of the present study was to investigate how the practice of different sports is distributed among different age groups and between men and women, by taking a picture of the medical certificate request in 2017 for sports in the population of the province of Modena, Italy. Methods. We analyzed the difference in distribution of requested medical certificate from 18 874 males and 7625 females stratified for age (<18 years, 18-40 years, and >40 years) and for different sporting disciplines (athletics, football, bike, swimming, basketball, volleyball, tennis, other team sports, other individual sports, and disabled sports). Results. Men requested medical certificates more than women (more than 2.5 times). The distribution of requested certificates differs significantly (chi-square test P < .0001) at different ages and between males and females of same age. Certificate for men aged less than 18 years were 7550 and for women were 4131 and the difference increase with age. Conclusions . In order to decrease the imbalance between men and women access to sports, it is mandatory to promote a healthy lifestyle and reduce, as consequence, cardiovascular risks, mostly in women after 40 years.